Food microbiology : fundamentals and frontiers - Doyle, Michael P.; Buchanan, Robert, 1946- (American Society for Microbiology Press, 2013)
This essential reference emphasizes the molecular and mechanistic aspects of food microbiology in one comprehensive volume.
"American Society for Microbiology."
Keywords: Food -- Microbiology.; elektronické knihy; electronic books